2018
DOI: 10.1088/1361-6439/aaf60d
|View full text |Cite
|
Sign up to set email alerts
|

Elastic–plastic characterization of microstructures through pull-in 4 point bending test

Abstract: This paper presents a simple design of gold MEMS, with a central test specimen undergoing tensile loading, for the experimental characterization of elastic-plastic behavior using electrostatic actuation. A kinematic model for the test microstructures is presented that relates the experimentally measured deflection in the test specimen to the developed axial and bending stress. Moreover, an elastic-plastic beam bending model is presented to analyze the development of plastic hinges in the central test specimen.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 45 publications
1
4
0
Order By: Relevance
“…Moreover, for the first three cycles the plastic zone is localized near the notch root, whereas further from this region the gold material remains unyielded and, thus, all the three specimens fully recovered to their initial positions after each loading cycle. As authors have already shown in [19], the progressive variation in the vertical deflection values of the three specimens each loading cycle can be attributed to the elasto-plastic behavior of the gold material with the initiation and progressive expansion of the plastic hinge in the critical locations of concentration, i.e. near the notch root of the specimens.…”
Section: Experimental Elasto-plastic Behavior Of the Notched Specimen...supporting
confidence: 55%
See 2 more Smart Citations
“…Moreover, for the first three cycles the plastic zone is localized near the notch root, whereas further from this region the gold material remains unyielded and, thus, all the three specimens fully recovered to their initial positions after each loading cycle. As authors have already shown in [19], the progressive variation in the vertical deflection values of the three specimens each loading cycle can be attributed to the elasto-plastic behavior of the gold material with the initiation and progressive expansion of the plastic hinge in the critical locations of concentration, i.e. near the notch root of the specimens.…”
Section: Experimental Elasto-plastic Behavior Of the Notched Specimen...supporting
confidence: 55%
“…The Fogale-Zoomsurf 3D optical profiling system is based on non-contact optical interferometry. The recorded light intensity is detected by a CCD pixel as a function of the specimen height, thus defining either the profile of the monitored specimen or its vertical position [19]. The optical view of sample is converted to an elevation map using interferogram processing techniques.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A test microstructure is specifically designed and built to characterize the fatigue fracture in gold-based MEMS notched specimen with on-chip testing. The design of the test microstructure, as well as its fabrication process and the advantages over other designs proposed in the literature, are extensively reported in authors' previous works [32,33,[45][46][47], thus just a brief description is given below for the sake of clarity.…”
Section: Test Microstructure Designmentioning
confidence: 99%
“…A summary of RFS microfabrication process steps is widely described in [28,50,51]. It is important to point out that the fabrication process is designed to limit the onset of residual stress, as explained in detail in previous authors' works [45,46,52]. The design of the test microstructure is addressed to correlate the degradation of the specimen stiffness due to cycling to the variation in the device deflection, as previously reported in [32,33,47].…”
Section: Test Microstructure Designmentioning
confidence: 99%